Analisis Perbandingan Performansi Protokol Routing OLSR dan SOLSR Pada Wireless Mesh Network - Sofyan Ainurrachman; Adhitya Bhawiyuga; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The performance of the routing protocol is a measure of the reliability of routing protocol. Routing protocol is a protocol that exchanges information in the form of a routing table to find the fastest route in sending data from the source node to destination node. OLSR is a proactive routing protocol that update it's topology information within a certain periode. OLSR protocol applies MPR mechanism to prevent some node receive a duplicate control message. SOLSR is a routing protocol based on OLSR with additional security mechanisms i.e signature message and timestamp exchange. Wireless mesh network (WMN) is a wireless network that formed from nodes which forming a mesh topology. The additional security mechanism in SOLSR routing protocol can affect the performance of the routing protocol itself. This research was conducted by measuring network performance of WMN with OLSR and SOLSR routing protocol. In addition, in this research author also make an attack simulation on routing protocol like replay attack and packet sniffing to examine the effect of attacks to performance of routing protocol both OLSR and SOLSR. Wireless mesh network (WMN) are formed from 5 router and 2 client. Based on result of this research, it is known that the additional security mechanisms in SOLSR affect the performance values under OLSR in self-configure time parameter and QOS performance on multihop network, but for the self-healing time between two routing protocols is not much different. In the attack simulation on routing protocol, it is known that the security mechanism on SOLSR can overcome the replay attack.